TECHNOLOGIES FOR THE DEVELOPMENT OF CRITICAL THINKING IN PRIMARY SCHOOL STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The introduction of the technology for the development of critical thinking in the current 21st century primary education system has become an urgent topic the main reason for this is due to the researchers ' views on the possibility of the formation of critical thinking [1]. Critical thinking is the ability of an individual to overcome a specific tendency to dogmatic perception, to analyze one or another problem, to use it. Information from various sources that distinguish objective reality is subjective opinion about it, logical conclusion assumptions or prejudice in various biases, the ability of a person to adequately identify, the causes and conditions of problems in his life, readiness to act are signified by their practical (not only rhetorical) resolution. The technology for the development of critical thinking can also be included as methods of educating a modern active personality [3].